Penambahan Gula Aren dan Krim dalam Kopi Gambir - Framida, Framida; Santoso, Budi; Wijaya, Agus; Priyanto, Gatot (Seminar Nasional Lahan Suboptimal, 2022)
Framida F, Budi S, Wijaya A, Priyanto G. 2022. Adding palm sugar and vegetable creamer on gambier coffee. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 368-387. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Gambir coffee has a high content of chlorogenic acid so it is very good for health, but it is necessary to improve the taste because of its bitter taste so palm sugar is chosen because it has a lower glycemic index of 35 and vegetable creamer which contains high saturated fatty acids so it is more stable to oxygen and oxygen. long term rancidity. This research aimed to determine the effect of addition palm sugar and vegetable creamer to the chemical and sensory characteristics of gambir coffee. This research used a Factorial Completely Randomized Design (RALF) with 3 factors and was repeated 3 times. Treatment factors include the addition of palm sugar and vegetable creamer with concentrations (b/b) of 20g, namely 20% (4g), 40% (8g) and 60% (12g). Parameters observed included chemical characteristics (moisture content, ash content, total phenol, antioxidant activity, total sugar and pH) and sensory characteristics using a preference test, included color, aroma and taste. The results showed that the addition of palm sugar and vegetable creamer was significantly affected the ash content, total phenol, antioxidant activity, total sugar, pH, and taste on sensory parameters. Gambir coffee with the addition of palm sugar 40% (8g) and vegetable creamer 60% (12g)  was the best treatment with preference test (2.92 for color; 3 for aroma and 2.92 for taste). and chemical characteristics was in accordance with SNI standard for ground coffee, namely water content 5.82%; ash content 4.09%; total phenol 17.32 mgGAE/g; IC50 140.82 ppm; total sugar 11.70% and pH 8.17.